"Foreign aid : diplomacy , development , domestic politics" - "Lancaster , Carol" (Chicago, 2007)
The question this book asks is "Why is aid given?" The question may seem odd since, after a half century of aid-giving, aid is a familiar and expected element in relations between states. And yet, in the middle of the first dec ade of the twenty-first century, foreign aid is much in the news. After major declines during the 1990s, aid levels are again rising. Aid's purposes are still debated, but development aid-apparently headed for extinction in the 1990s-is making an impressive comeback.
Keywords: Economic assistance